2019
DOI: 10.1016/j.nedt.2018.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students' trait mindfulness and psychological stress: A correlation and mediation analysis

Abstract: Background: Nursing students face a great amount of psychological stress during their nursing education. Mindfulness-based training has received increased recognition from nurse educators regarding its effect on reducing students' psychological stress. Study evidence has supported that cultivation of trait mindfulness through Mindfulness-based training was the key to this effect. However, there is a lack of research that focuses on intricate relationships between various facets of trait mindfulness and psychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 24 publications
5
19
0
3
Order By: Relevance
“…The present study indicated that mindfulness is associated with occupational burnout in three dimensions, which are emotional exhaustion, depersonalization and personal accomplishment. Lu et al observed that mindfulness is correlated with psychological stress in nursing students, corroborating this study (Lu et al., 2019). Based on proved correlation, further analysis of the mediating effect proved that mindfulness can directly negatively affect emotional exhaustion and depersonalization.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The present study indicated that mindfulness is associated with occupational burnout in three dimensions, which are emotional exhaustion, depersonalization and personal accomplishment. Lu et al observed that mindfulness is correlated with psychological stress in nursing students, corroborating this study (Lu et al., 2019). Based on proved correlation, further analysis of the mediating effect proved that mindfulness can directly negatively affect emotional exhaustion and depersonalization.…”
Section: Discussionsupporting
confidence: 85%
“…observed that mindfulness is correlated with psychological stress in nursing students, corroborating this study (Lu et al, 2019). Based on proved correlation, further analysis of the mediating effect proved that mindfulness can directly negatively affect emotional exhaustion and depersonalization.…”
Section: The Direct Effect Of Mindfulness On Emotional Exhaustion Asupporting
confidence: 85%
“…Consistent results were found in many previous studies. Mindfulness was negatively correlated with stress in studies of nursing students in Korea [ 52 ] and the United States [ 53 ]. In a study of university students in Malaysia, mindfulness was reported to be negatively correlated with stress; it reduced stress and acted as a mediator between negative mental health outcomes [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rather than a causal relationship directly associated between HL (IV) and PP (DV), the mediation model proposes that the IV (HL) affects the intervening or intermediary variable (THI), which in turn, affect the DV (PP) (Bellavia, James-Todd, & Williams, 2019). Therefore, the intermediary variable (THI) clarifies the nature of the relationship between the proposed model’s IV (HL) and DV (PP) (Lu et al, 2019). The mediation model helps researchers obtain a clearer understanding of the relationship between the selected IV (HL) and DV (PP) (Abbas, Aman, Nurunnabi, & Bano, 2019; Abbas, Aqeel, et al, 2019; Abbas, Aqeel, Wenhong, Aman, & Zahra, 2018; Abbas, Raza, Nurunnabi, Minai, & Bano, 2019).…”
Section: Methodology Sectionmentioning
confidence: 99%